An exploration of origin of life for exoplanetary science - Keller, Finnegan; Kataria, Tiffany; Barge, Laura M.; Chen, Pin; Yung, Yuk; Weber, Jessica M. (Frontiers in Astronomy and Space Sciences, 2025)
The factors that enable life to begin define the difference between an inhabited planet and one that is simply habitable. While used extensively in Origins, Worlds, and Life: A Decadal Strategy for Planetary Science and Astrobiology 2023–2032 (abbreviated “OWL” in this paper), the term origin of life is never mentioned in Pathways to Discovery in Astronomy and Astrophysics for the 2020s (notated as “Astro2020” in this paper). While the chapters on the search for life in the solar system in OWL treat the origin of life as a central concept, the exoplanet focused chapters of the OWL and Astro2020 reports mostly do not mention origin of life science, particularly with respect to how it intersects with biosignature identification and interpretation. To begin to fill this gap, we describe the set of conditions that are required for life to begin and suggest that they may be distinct from those that make an environment habitable. Finally, we present a putative list of origin of life processes that may be observable on exoplanets and outline the relevance of future planetary science and astrophysics missions to this topic. Given the complexity of detecting these conditions beyond the solar system, we argue that while looking for signs of the origin of life on exoplanets could be fruitful in determining which are worthy of further study, the concept is likely more appropriate for distinguishing true biosignatures from false positives. Ensuring that future facilities like the Large Interferometer For Exoplanets (LIFE) and the Habitable Worlds Observatory (HWO) can constrain origin of life conditions is necessary for life detection searches beyond the solar system.